A Strategic Management Approach to Reduce Pepper Weevil Damage to Jalapeño Pepper Plants with Conventional and Biorational Insecticides - Naga Mani Kanchupati; Dakshina R. Seal; Bruce Schaffer; Oscar E. Liburd (Agronomy)
The pepper weevil (Anthonomus eugenii) is a major pest that causes significant economic damage to several species and cultivars of pepper, including jalapeño (Capsicum annuum var. jalapeño). Protecting pepper crops from this pest often necessitates the use of chemical insecticides. To enhance control measures and mitigate the risk of insecticide resistance in the pepper weevil, this study focused on determining the optimal timing and application intervals of thiamethoxam and isocycloseram and assessed the effectiveness of rotating these pesticides with biorational insecticides. The effectiveness of various spray intervals for thiamethoxam and isocycloseram, starting at the bloom stage and one week post-bloom, was also assessed on the management of pepper weevils. The spray intervals for each insecticide included foliar applications weekly, every two weeks, every three weeks initiated at the blooming stage, and every two weeks beginning one week after blooming. The application of thiamethoxam and isocycloseram starting at bloom at one-week (7.3 ± 0.9 and 0.6 ± 0.4) and two-week (7.3 ± 0.9 and 0.7 ± 0.2) intervals significantly reduced the number of pepper weevil-infested buds compared to the untreated control (18.3 ± 2.5 and 1.7 ± 0.2). Isocycloseram starting at bloom and rotated with azadirachtin + pyrethrins as well as isocycloseram rotated with azadirachtin + pyrethrins and thiamethoxam on a weekly basis had the lowest number of pepper weevil-infested buds, flowers, and fruits and higher marketable yield. These findings suggest that adopting foliar applications weekly or every two weeks starting at bloom, as well as the rotation of thiamethoxam and isocycloseram with biorational insecticides, can effectively reduce pepper weevil infestation and increase pepper yield.